Design and optimization on rootstock cutting mechanism of grafting robot for cucurbit - Jiang, Kai; Zhang, Qian; Chen, Liping; Guo, Wenzhong; Zheng, Wengang (International Journal of Agricultural and Biological Engineering, 2020)
Cutting mechanisms in existing grafting machines are unable to completely cut through the rootstock growth point and can easily damage seedlings. During the mechanical operation of splice grafting, the cutting angle of the rootstock is an essential factor for ensuring the quality and survival rate of grafting seedlings and a stable process for grafting robots. Therefore, in this study, commonly used grafting rootstocks, e.g., cucurbita moschata, and calabash gourd were used as research objects for studying and analyzing the cutting angle of a splice grafting method. The morphological and structural parameters of the rootstock and scion were measured, and a structural model of the internal cavity of the rootstock was constructed using an image analysis method. The critical cutting angles for the cucurbita moschata and calabash gourd seedlings were obtained. According to the analysis, the grafting cutting angles for cucumber seedlings matching with cucurbita moschata seedlings were 20° and 25°, respectively, and the fitting rate of the cutting surface of the rootstock and scion was 99.04%. A cutting mechanism for the rootstock growth point and geometric model of the cutting operation were established, and the structural parameters of the mechanism and cutting angle adjustment were optimized. A cutting performance test showed that the success rate of the pressing the cotyledons of cucurbita moschata seedlings was 96.67%, and the success rate of cutting was 98%. The cutting accuracy was 96.8%, and the cutting surface fitting rate of the rootstock and scion was 98.61%. The latter differed by 0.43% from the theoretical rate but met the requirements for the splice grafting method. Thus, this study can provide a reference for the design of a cutting mechanism for a grafting robot.Keywords: grafting robot, rootstock cavity, cutting angle, matched grafting, parameter optimization, cucurbitDOI: 10.25165/j.ijabe.20201305.5803Citation: Jiang K, Zhang Q, Chen L P, Guo W Z, Zheng W G. Design and optimization on rootstock cutting mechanism of grafting robot for cucurbit. Int J Agric & Biol Eng, 2020; 13(5): 117–124.